STRATEGY FOR IMPLEMENTING WORK SAFETY CULTURE IN THE PT ENVIRONMENT. WIJAYA KARYA (PERSERO) TBK, OPERATIONS DEPARTMENT 1 (SUMATRA REGION) - Dody Hariyanto; Harmein Nasution; Yeni Absah (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
Safety culture is a concept defined at a group level or higher that refers to the shared values ​​between all groups or companies, corporations, or organizational members. Safety culture relates to formal safety issues within an organization and is closely related to, but not limited to, management and supervision systems. A safety culture emphasizes the contributions of everyone at every level of the organization. In business entities this impacts the behavior of all workforce members in the workplace which is usually reflected in the relationship between reward systems and safety performance. This research examines how much regulatory factors and management commitment can influence the implementation of safety culture, as well as what strategy suggestions can be made to improve safety culture. The research was conducted within the PT. Wijaya Karya (Persero) Tbk Operations Department 1 Sumatra Region using the Explanatory Sequential Design method or known as the two-phase method where quantitative data as the first phase is used as a base and qualitative data as the second phase for supporting, or in other words the quantitative approach is the main priority which is supported by a qualitative approach (Sinulingga, 2021), Qualitative research using Likert questionnaires was carried out on 44 employees from various positions, as well as qualitative interviews as support for the 4 selected employees. From the research results, it was found that regulations and management commitment have an important influence on safety culture, both partially and jointly. This strategy can work well if management has a full commitment to making safety culture part of the company culture. Without this, inconsistencies and tolerance for deviations will arise, which if left unchecked will hamper or possibly thwart the process of creating the expected safety culture.